Hubungan Self-Compassion dengan Flourishing Pada Mahasiswa Yang Mengikuti Organisasi di Fakultas Psikologi UIN Sultan Syarif Kasim Riau - Shafaira, Cinta; Yulianti, Alma (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
Backround: Students who participate in organizations have a dual role, as academics and organizers. Students who participate in organizations are often faced with various situations that have an impact on the level of flourishing. Objectives: The purpose of this study was to determine the relationship between self-compassion and flourishing in students who participate in organizations. Method: The sampling technique in this study was saturated sampling technique. The subjects in this study were 98 students who participated in organizations at the Faculty of Psychology, UIN Sultan Syarif Kasim Riau. The measuring instrument in this study used the Self-Compassion Scale with a reliability coefficient of 0.868 and The PERMA Profiler with a reliability of 0.980. Result: The results of this study indicate that there is a positive relationship between self-compassion and flourishing in students who participate in organizations. This is evidenced by the correlation coefficient value (r) = 0.615 and sig 0.000, meaning that there is a relationship between self-compassion and flourishing in students who participate in student organizations at the Faculty of Psychology UIN Sultan Syarif Kasim Riau. Conclusion: The implication of this research is that self-compassion is one of the factors that can increase flourishing in students. So that students who take part in organizations at the Faculty of Psychology UIN Sultan Syarif Kasim Riau can maintain and improve the quality of self-compassion in themselves by maintaining and continuing to improve the ability of aspects of self-compassion.